2004
DOI: 10.1111/j.1365-3091.2004.00671.x
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentation and recent history of a freshwater wetland in a semi‐arid environment: Loboi Swamp, Kenya, East Africa

Abstract: Loboi Swamp is a 1·5 km2 freshwater wetland situated near the equator in the Kenya Rift Valley. The climate is semi‐arid: precipitation is ≈ 700 mm year−1, and evapotranspiration is ≈ 2500 mm year−1. Some of the wetland water is currently used for irrigation. An interdisciplinary study was conducted on the geology, hydrology, pedology and biology of the wetland to determine its origin and history and to assess its longevity under present hydrological conditions. Sedimentary records from two piston cores (1·8 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(52 citation statements)
references
References 52 publications
4
48
0
Order By: Relevance
“…) and has a higher pH (7.4-8.3) (Ashley et al 2004). Comparatively, Crocodile Lake is a crater formed island lake within the Lake Turkana.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…) and has a higher pH (7.4-8.3) (Ashley et al 2004). Comparatively, Crocodile Lake is a crater formed island lake within the Lake Turkana.…”
Section: Methodsmentioning
confidence: 99%
“…) and slight acidity pH (6.4-6.9) (Ashley et al 2004). The springs drain into Loboi swamp of about 1.5 km 2 , which is covered by dense vegetation of Typha domingensis and Cyperus papyrus.…”
Section: Methodsmentioning
confidence: 99%
“…The cores were retrieved with a rod-operated single-drive piston corer (Wright, 1980) operated from the mud surface. The core site was selected with proximity to Ashley's et al, [14] previous core site as main reference (Figure 1), however better accessibility aided by reduced water levels within the wetland made it possible to access part of the deepest area on the western side of the wetland. The longest core section, LOB14-1P I, measured 101.8 cm and reached almost to the base of the swamp deposit.…”
Section: Methodsmentioning
confidence: 99%
“…The swamp is fed by water from three main surface springs: Lake Bogoria spa spring, Chelaba spring and Turtle spring. Due to the consistent seepage and flow of the springs, it is suggested that local aquatic ecosystems may have persisted even during past episodes of severe climatic aridity when Lake Baringo and other Rift lakes stood completely dry [14]. Loboi Swamp serves an important role of habitat provision for a wide range of biodiversity.…”
Section: Study Areamentioning
confidence: 99%
“…GWD deposits are preserved globally in the geologic record, contain information on the timing and magnitude of past changes in water table levels, and are a source of paleohydrologic and paleoclimatic information (4)(5)(6)(7)(8)(9)(10). Previous studies have shown that desert wetlands in the southwestern United States responded to climate change at glacial to interglacial timescales (e.g., refs.…”
mentioning
confidence: 99%